Treatment Options for Postinflammatory Hyperpigmentation in Color Skin - Putri Hendria Wardhani; Rahmadewi Rahmadewi (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2016)
Background: Post inflammatory hyperpigmentation (PIH) is a reactive hypermelanosis after inflammation. PIH can have a negative impact on a patient’s quality of life, particularly for darker-skinned patient. Although PIH can occur in any skin type, but this type of hypermelanosis is more common in color skin patients. Purpose: Review treatment options for HPI in color skin. Review: Skin of color describes individuals with increased epidermal pigment and darker skin. This subset of patients has unique cosmetic concerns and often requires special consideration for cosmetic procedures. PIH is more frequent, more severe dan more evident in color skin. Conclusion: Treatment for the underlying dermatosis and sunscreens are an effective treatment. Topical treatment is effective for PIH epidermal only. Hydroquinone in combination with topical steroid, retinoid, glycolic acid, lactic acid as well as kojic acid, arbutin, ascorbic acid, soy, and niacinamide. Salicylic acid and glycolic acid chemical peeling as well as quality-switched (QS) neodymium-doped yttrium aluminum garnet (Nd: YAG) laser, QS Ruby, 1550 nm erbium fiber fractional thermolysis, and 1927 nm fractional thulium fiber shows a good efficacy for facial hyperpigmentation treatment.